2020
DOI: 10.37940/ajvs.2020.13.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Histological Changes of Urogenital Tract in Albino Rats

Abstract: This study was conducted to investigate the histologic changes of kidney, urinary bladder, testis, seminal vesicle and prostate gland of rats of various ages (6,12 and 18 months old). Results illustrated variable changes of kidney represented by congestion of renal capillaries, acute tubular necrosis, shrinkage of glomerular tuft, degeneration in tubular epithelium of the 6,12 and 18 months old rats, the morphometric changes of the glomerular diameter decreases with advanced age. The lesions of urinary bladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We demonstrated that the bladder wall is a highly mechanical heterogeneous tissue, characterized by a gradient of stiffness from urothelium to lamina propria and muscle layer. We also showed an effect of aging on tissue mechanics, which is known to alter murine bladder histology 25 . Understanding tissue mechanics and the distribution corresponding to different anatomical tissue layers -as it was previously reported for organs as the cornea 26 or the skin 27 -is also of relevance for the bladder, as its physiological function comprehends high elastic tension and mechanical stress, and it may be crucial for bladder reconstruction purposes.…”
Section: Discussionmentioning
confidence: 64%
“…We demonstrated that the bladder wall is a highly mechanical heterogeneous tissue, characterized by a gradient of stiffness from urothelium to lamina propria and muscle layer. We also showed an effect of aging on tissue mechanics, which is known to alter murine bladder histology 25 . Understanding tissue mechanics and the distribution corresponding to different anatomical tissue layers -as it was previously reported for organs as the cornea 26 or the skin 27 -is also of relevance for the bladder, as its physiological function comprehends high elastic tension and mechanical stress, and it may be crucial for bladder reconstruction purposes.…”
Section: Discussionmentioning
confidence: 64%
“…In Thi Qar city, a study of the parasitic and bacterial infections associated with appendicitis is carried out and reported four parasitic species; E. histolytica, G. lamblia, A. lumbricoids and E. vermicularis [11]. Another study in Samara district, also recorded four species E.histolytica, Entamoeba coli, E. vermicularis and Taenia saginata [12]. In Kirkuk city the parasitic infections associated with appendicitis aren't studied; according to the mentioned above the objective of the present study is the diagnosis of the parasitic infections in resected appendices in patients with appendicitis in Kirkuk city, in addition to determining its relationship with age, gender and stage of reported parasites species.…”
Section: Introductionmentioning
confidence: 99%